PHYSICAL CHARACTERISTICS OF FRUIT, BEANS, AND POWDER OF COFFEE HARVESTED FROM SINDANG JATI VILLAGE, REJANG LEBONG DISTRICT - Oriza Sativa; Yuwana Yuwana; Bonodikun Bonodikun (Jurnal Agroindustri, 2014)
Most of farmers especially in Rejang Lebong, Bengkulu, cultivaterobusta coffee.Through the preliminary observations there have been obtained bad post harvest handling, as the fruit cherries mixed green, yellow, and red; that reduced quality of coffee beans from smallholder plantations. To improve yields and product, good attention to farmers harvest, harvesting the coffee berries have a decent harvest to be able to compare the different characteristics of the coffee fruit.This research using Chi-square analysis to calculate significant difference or not in the process harvesting different ways, and using ANOVA analysis and LSD (Least Significant Difference) to calculate the real difference or not significantly different in mass density, spersitas fruit fresh coffee and coffee beans. Based on the Chi-square analysis obtained differences in the percentages of different crops on fresh fruits (red, yellow, green) with a different way of harvest. Based on the analysis of ANOVA and LSD test obtained density difference, spersitas there are distinct differences between coffee red, yellow and green